1968
DOI: 10.1063/1.1668881
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quenching Via Charge Transfer: The Perylene-N,N-Dimethylaniline System

Abstract: The mechanism of fluorescence quenching in a system where there was evidence that quenching proceeds via a charge-transfer complex has been investigated using the direct observation of fluorescence decay as a tool to explore the kinetics of the quenching process. The system studied was perylene in its fluorescent state quenched by amines in a variety of solvents with dielectric constants ranging from 2.3 to 37. In solvents with dielectric constant greater than 12, the fluorescence decay is exponential and no C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1969
1969
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…9). There is considerable experimental evidence to show that singlet oxygen is not predominant in strong alkali solution [19]. Lu and Lu [10] studied the CL from the luminol-H 2 O 2 -ClO À system.…”
Section: Luminol Ecl At the Cathodementioning
confidence: 99%
“…9). There is considerable experimental evidence to show that singlet oxygen is not predominant in strong alkali solution [19]. Lu and Lu [10] studied the CL from the luminol-H 2 O 2 -ClO À system.…”
Section: Luminol Ecl At the Cathodementioning
confidence: 99%
“…Detailed investigations have been made for aromatic hydrocarbon-aromatic amine exciplexes in various solvents, and it has been shown that exciplex formation is a rapid diffusion-controlled process [3].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, tremendous effort has and is still being invested to understand the fine details of both intra-and intermolecular charge transfer (CT) processes. 2,3 Although an impressively large number of molecular systems, going from directly linked DA compounds to highly sophisticated architectures of D and A units, have been elaborated, [4][5][6][7][8][9] and although DMA and Pe represent a prototypic pair for intermolecular electron transfer studies, 1,[10][11][12][13][14][15][16] intramolecular CT in covalently linked PeDMA has never been investigated so far.…”
Section: Introductionmentioning
confidence: 99%